2005
DOI: 10.1038/sj.cdd.4401645
|View full text |Cite
|
Sign up to set email alerts
|

Induction of annexin-1 during TRAIL-induced apoptosis in thyroid carcinoma cells

Abstract: We investigated the expression of annexin-1 (ANXA1) in thyroid carcinoma cell lines and in thyroid cancers with a different degree of differentiation. The highest level of ANXA1 expression examined by Western blotting was detected in the papillary carcinoma cells (NPA) and in the follicular cells (WRO). On the other hand, the most undifferentiated thyroid carcinoma cells (ARO and FRO) presented the lowest level of ANXA1 expression. In surgical tissue specimens from 32 patients with thyroid cancers, we found hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 4 publications
2
29
0
Order By: Relevance
“…ANXA1 plays a role in phospholipase A2 activity (Solito et al 2003), as well as mediating apoptosis (Petrella et al 2005). Therefore, it is logical that ANXA1 was dramatically up-regulated in the regressed CL in comparison with the functional CL (this study).…”
Section: Signal Transduction and Apoptosismentioning
confidence: 89%
“…ANXA1 plays a role in phospholipase A2 activity (Solito et al 2003), as well as mediating apoptosis (Petrella et al 2005). Therefore, it is logical that ANXA1 was dramatically up-regulated in the regressed CL in comparison with the functional CL (this study).…”
Section: Signal Transduction and Apoptosismentioning
confidence: 89%
“…Bid, a member of the Bcl2 proapoptotic family, is cleaved to tBid by the initiator caspase-8 upon activation, myristoylated by myristoyl-CoA: protein N-myristoyltransferase before relocalization to mitochondria for the signaling of cytochrome c release (35) from the mitochondria, a characteristic of the intrinsic pathway (36,37). Previous studies have shown that ANXA1 is a proapoptotic protein that can regulate tumor necrosis factor-related apoptosis-inducing ligand-induced cell death in follicular thyroid carcinoma cells through the regulation of Bcl-2/Bcl-X Lassociated death promoter activity and translocation to the mitochondria (38). In addition, neutrophil apoptosis is induced by ANXA1 in a calcium-dependent manner and through the dephosphorylation of Bcl-2/Bcl-X L -associated death promoter (39).…”
Section: Discussionmentioning
confidence: 99%
“…36 In addition, ANXA1 expression is strongly induced in thyroid carcinoma cells during ''tumor necrosis factor-related apoptosis inducing ligand'' (TRAIL)-induced apoptosis. 37 Preliminary experiments by us to investigate if treatment with peptide Ac2-26 (2 lM) influenced apoptosis in Hep-2 cells revealed that there was no increase in apoptotic cell number as identified by ANXA5 binding (data not shown). Another possible mechanism for the antiproliferative action of ANXA1 could be via activation of the extracellular receptor kinase (ERK) signaling cascade, as previously demonstrated in a variety of cell types.…”
Section: Discussionmentioning
confidence: 99%